2021
DOI: 10.1093/ehjqcco/qcab091
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the 2020 COVID-19 pandemic on the implantation rates of cardiac implantable electronic devices in Germany: changes between 2020 Q1–Q3 and 2019 Q1–Q3

Abstract: Aim During the early phase of the COVID-19 pandemic, hospital admissions for several medical and surgical conditions have declined. Few data are available with respect to elective cardiac implantable electronic devices (CIEDs) implantation. The aim of the present study was to determine the impact of the COVID-19 pandemic on the monthly CIED implantation rates in Germany. Methods and Results The monthly rates of CIED implantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Also in Germany, these trends were confirmed, with a drop in CRT-Ds similar to that observed by our study [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Also in Germany, these trends were confirmed, with a drop in CRT-Ds similar to that observed by our study [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…During the early phase of the COVID-19 pandemic, CIED implantations decreased by 56.5% in northeastern Spain ( 9 ), 39.38% in Poland ( 12 ), 28% in the Veneto region of Italy ( 10 ), and 48% in northwestern Greece ( 13 ). In agreement with these reports, the number of CIED implantations in China also decreased significantly in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, cardiology societies have issued guidelines recommending the postponement or cancellation of any non-urgent elective procedures to conserve healthcare resources, including the placement of cardiac implantable electronic devices (CIED) (7). Focusing on the early stages of the outbreak, studies from several countries have reported a substantial reduction in the number of cardiac interventions (8)(9)(10)(11)(12)(13)(14)(15)(16). However, the survival benefits of CIED implantation have been clearly established (17), and delayed implantation may lead to poor patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A German study showed that the pandemic was associated with an overall decline of device implantation rates of -2.6%, with a peak of almost -23%[ 61 ]. This situation was limited in time.…”
Section: Cardiac Arrythmiasmentioning
confidence: 99%